From three congregations to one autonomous church: The Swaziland Reformed Church - Wyngaard, Arnau van (HTS teologiese studies, 2018)
This article covers the time from 1985 to 1992 in the history of the Swaziland Reformed Church (SRC). In 1985, for the first time in its existence, the SRC had four missionaries working in the four districts of the country. At this stage the SRC formed a presbytery within the synodical region of the Dutch Reformed Church in Africa (DRCA) of Northern Transvaal. In 1989 – at its own request – this church became a regional synod within the DRCA. However, not long thereafter, in 1992, it was forced to become an independent Reformed church, even though it still remained part of the family of Dutch Reformed churches. Making use of original documents, this article records this history of the SRC.